Researching Men's Violence Against Women as Feminist Women Researchers: The Tensions We Face - Dheensa, Sandi (Violence against women, 2024)
Qualitative and feminist researchers aim to build rapport, show empathy, be non-judgemental, and equalise power imbalances. A crucial challenge researchers face is how to navigate and balance competing aims and values when interacting with and interviewing participants who have perpetrated intimate partner violence and abuse towards women. In this article, four female researchers evaluating perpetrator programmes for abusive men use reflexive analysis to identify the tensions encountered in such research. We outline how these tensions affected us and the data produced, and end with recommendations, which we hope will help prepare researchers, particularly women, for conducting interviews with violent/abusive men.